2014
DOI: 10.1038/nature12949
|View full text |Cite
|
Sign up to set email alerts
|

Within-group male relatedness reduces harm to females in Drosophila

Abstract: Resolving the mechanisms that switch competition to cooperation is key to understand biological organization1. This is particularly relevant for intrasexual competition, which often leads to males harming females2. Recent theory proposes that kin selection may modulate female harm by relaxing competition among relatives3-5. We experimentally manipulated the relatedness of groups of male Drosophila melanogaster competing over females to demonstrate that, as expected, within group relatedness inhibits male compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
194
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(214 citation statements)
references
References 42 publications
16
194
4
Order By: Relevance
“…Apparently, reduced competition between related males also reduced aggression against females who might be bearing the offspring of related males. Notably, reduced aggression also was observed in situations where not all males were related (36), indicating that the presence of related males may benefit both unrelated males and females across species as diverse as fruit flies and baboons.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Apparently, reduced competition between related males also reduced aggression against females who might be bearing the offspring of related males. Notably, reduced aggression also was observed in situations where not all males were related (36), indicating that the presence of related males may benefit both unrelated males and females across species as diverse as fruit flies and baboons.…”
Section: Discussionmentioning
confidence: 98%
“…Indirect fitness benefits also may play a role, however. A study of fruit flies (Drosophila melanogaster) showed that females which were kept with males that were related to each other experienced less aggression than females kept with unrelated males (36). Apparently, reduced competition between related males also reduced aggression against females who might be bearing the offspring of related males.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, males acted equally as antagonistically towards their sisters as they did towards unrelated females. In their study, Carazo et al [11] had suggested that males modulate aggression when housed with kin to reduce the magnitude of harm done to brothers and to shared mates, thereby increasing indirect fitness gains. However, our study, like that of Chippindale et al [31], reveals no such fitness benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Hollis et al [29] argued that by failing to properly control for developmental and social familiarity between relatives, the results of Carazo et al [11] cannot be clearly interpreted as arising due to kin selection alone. Specifically, Hollis et al [29] argued that increased male-male aggression in the unrelated males treatment could be an artefact of the pre-trial developmental conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation